2018
DOI: 10.1097/md.0000000000009014
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and sexual behavior among young male conscripts in the Brazilian army, 2016

Abstract: Since 1996, the Brazilian Department of Sexually Transmitted Infections (STI), AIDS and Viral Hepatitis (Departamento de Vigilância, Prevenção e Controle das IST, do HIV, AIDS e Hepatites Virais, Secretaria de Vigilância em Saúde, Ministério da Saúde) in collaboration with the Brazilian Ministry of Defense has conducted periodic and anonymous probability sample surveys to determine the human immunodeficiency virus (HIV) prevalence, the sexual and risk behaviors among conscripts of the Brazilian army. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 10 publications
1
27
0
16
Order By: Relevance
“…The main reasons for LD are the absence or low perception on the risk on the part of vulnerable people ( 38 - 39 ) . Generally, people with a steady affective partnership, due to the low perception of risk ( 37 ) , use condoms less frequently during sexual intercourse, which makes them vulnerable to HIV ( 40 ) and to late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for LD are the absence or low perception on the risk on the part of vulnerable people ( 38 - 39 ) . Generally, people with a steady affective partnership, due to the low perception of risk ( 37 ) , use condoms less frequently during sexual intercourse, which makes them vulnerable to HIV ( 40 ) and to late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was conducted among MSM aged 18 years and over, 58.3% of them younger than 25 years of age 24 . Sperhacke et al 1 identified that in 2016 the prevalence of HIV among Brazilian conscripts who declared themselves as MSM was 1.32%, while for the total sample the prevalence was 0.12%.…”
Section: Condom Use In Every Sexual Intercourse With Occasional Partnmentioning
confidence: 99%
“…National and international surveys have indicated a greater vulnerability of adolescents and young men to STIs, particularly HIV infection [1][2][3][4] . In Brazil, data from the latest HIV/AIDS Epidemiological Bulletin 5 indicated that, from 2007 to 2017the AIDS detection rate increased approximately 2.3 times among men aged 15 to 19 (from 3 to 7/100 thousand inhabitants) and 20 to 24 (from 15.6 to 36.2/100 thousand inhabitants).…”
Section: Introductionmentioning
confidence: 99%
“…Inquéritos nacionais foram realizados junto à chamada população geral, como as pesquisas sobre "Comportamento Sexual e Percepções da População Brasileira sobre HIV/Aids", realizadas em 1998 e 2005, em amostras representativas da população brasileira de 16 a 65 anos pelo Centro Brasileiro de Análise e Planejamento (CEBRAP); e as Pesquisas de Conhecimentos, Atitudes e Práticas relacionadas às DST e Aids (Brasil, 2005(Brasil, , 2011, inquéritos domiciliares realizados em 2004 e 2008 representativos da população brasileira de 15 a 64 anos; e as pesquisas entre jovens conscritos do exército brasileiro realizadas desde 1996, cuja oitava edição foi realiza-da em 2016 (Szwarcwald et al, 2005;Szwarcwald et al, 2011;Sperhacke et al, 2018). Somente em 2009, o PN-DST/Aids passou a financiar a realização de estudos de vigilância comportamental e epidemiológica voltados aos grupos populacionais mais afetados pela epidemia, dedicando-se aos HSH, que incluíram, além de entrevistas sobre comportamentos sexuais e preventivos, a realização de testagem para HIV (Kerr et al, 2013(Kerr et al, , 2018.…”
Section: Prevalência E Prevençãounclassified